2002
DOI: 10.1161/01.cir.0000030995.59403.f8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging to Assess the Hemodynamic Effects of Pulmonary Valve Replacement in Adults Late After Repair of Tetralogy of Fallot

Abstract: Background-Pulmonary regurgitation (PR) late after total correction for tetralogy of Fallot may lead to progressive right ventricular (RV) dilatation and an increased incidence of severe arrhythmias and sudden death. Timing of pulmonary valve replacement (PVR) is subject to discussion, because the effect of PVR on RV function in adults is unclear. In this study, MRI was used to assess the effect of PVR on RV function and PR. Clinical improvement was established by means of the NYHA classification. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(192 citation statements)
references
References 25 publications
9
178
0
5
Order By: Relevance
“…The group of patients subjected to PPVI is varied in terms of primary diagnosis, symptoms, number of interventions, type of dominant lesion, and anatomy of the heart. Investigators try to define the baseline characteristics related to an improvement after PPVI, most typically acknowledged by the assessment of ventricular end-systole and end--diastole volumes, or CPET [11][12][13][14]. The reported factors that are believed to influence short-and/or long-term results include: type of dominant lesion [4,15]; baseline RVEDV [16,17]; and baseline peak VO 2 value [18].…”
Section: Discussionmentioning
confidence: 99%
“…The group of patients subjected to PPVI is varied in terms of primary diagnosis, symptoms, number of interventions, type of dominant lesion, and anatomy of the heart. Investigators try to define the baseline characteristics related to an improvement after PPVI, most typically acknowledged by the assessment of ventricular end-systole and end--diastole volumes, or CPET [11][12][13][14]. The reported factors that are believed to influence short-and/or long-term results include: type of dominant lesion [4,15]; baseline RVEDV [16,17]; and baseline peak VO 2 value [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary valve incompetence is usually seen in patients with tetralogy of Fallot following repair. (14) …”
Section: Volume Overloadmentioning
confidence: 99%
“…By 1996, it was used to measure RV volume in repaired TOF. 17,20 Vliegen and colleagues 21 showed that PR was eliminated and RV volume was reduced following PVR. However, the authors noted that the RV did always decrease to normal size.…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%
“…However, the authors noted that the RV did always decrease to normal size. 21 In 2005, Therrien and colleagues 22 showed that once the RV end-diastolic volume (RVEDV) reached 170 mL/m 2 and the RV end-systolic volume (RVESV) reached 85 mL/m 2 that remodeling to normal size following PVR was unlikely (Fig. 5).…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%